PENERAPAN GAYA KEPEMIMPINAN TRANSFORMASIONAL DALAM MANAJEMEN PONDOK PESANTREN HIDAYATUL FATIR DI KAMPUNG CIHERANG RT. 02,RW 04,DESA MAJA, KABUPATEN LEBAK, PROVINSI BANTEN - Ardhya, Bella Nanda (Gapenas Publisher, 2025)
Technological developments in the era of globalization have had a devastating impact on human life. They have brought about various disruptions. Under these conditions, individuals, especially leaders, must adapt to the rapid changes brought about by globalization. Technological advancements, for example, require leaders to adapt their leadership style to make quick decisions based on current conditions. This article discusses transformational leadership, which provides an answer to the leadership style of a leader in the era of globalization. This article utilizes qualitative research methods with data collection techniques from various sources, such as books and journals. This article utilizes the concept of transformational leadership, which provides an answer to leadership styles in the current era of globalization. This article argues that leaders with a transformational leadership style are more adaptive to globalization and impact progress in the organizations and companies they lead, accelerating their success. This article concludes that transformational leadership, with its characteristics, is the right answer for a leader in this era of globalization. Adaptability and composure, for example, are important factors for a leader in this era of technological disruption.